2020
DOI: 10.1029/2020jb020539
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Failure and Localization of Basalt at Temperature and Pressure Conditions Spanning the Brittle‐Ductile Transition

Abstract: Natural phenomena such as seismicity, volcanism, and fluid circulation in volcanic areas are influenced by the mechanical response of intact basalt. When subjected to a wide range of environmental loading conditions, basalt exhibits inelastic deformation characteristics ranging from brittle to ductile behavior. In this manuscript, we present a new constitutive model of basalt that spans the brittle-ductile transition by covering a wide range of mean effective stress, temperature, and strain rate. The model has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…The data that support the findings of this study are openly available in Zenodo (https://doi.org/10.5281/zenodo.4130851) and Pec and Al Nasser (2020).…”
Section: Data Availability Statementsupporting
confidence: 77%
“…The data that support the findings of this study are openly available in Zenodo (https://doi.org/10.5281/zenodo.4130851) and Pec and Al Nasser (2020).…”
Section: Data Availability Statementsupporting
confidence: 77%
“…Violay et al 2012Violay et al , 2015a and volcanic edifices (e.g. Bakker et al 2019;Parisio et al 2019Parisio et al , 2020. The strength and mechanical properties of volcanic rocks are also of important in the context of geothermal energy exploitation (Siratovich et al 2016;Eggertsson et al 2020;Weaver et al 2020;Heap et al 2020c;Weydt et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From the rheological observations, we show that hydro-fracturing attenuation occurs only once the material can accommodate very large values of plastic deformation without ultimate failure. Such a limit in igneous (even in certain metamorphic rocks) is believed to lie well above the limit of C 27 29 . Evidence suggests that at C, hydro fracturing occurs through fluid percolation: micro-cracks and an increase in permeability have been observed in post-mortem samples 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Evidence suggests that at C, hydro fracturing occurs through fluid percolation: micro-cracks and an increase in permeability have been observed in post-mortem samples 5 . Natural seismicity is known to occur well above C and possibly even C 27 , and brittle-ductile transition models have shown that the presence of fractures and faults is almost certain in such high temperature conditions 29 . Furthermore, drilling of the IDDP-2 well has generated induced seismic events at temperatures above C 6 and the high permeability recorded is likely associated with permeable fractures.…”
Section: Discussionmentioning
confidence: 99%